Avian influenza viruses inhibit the major cellular signalling integrator c‐Abl. (26th August 2014) - Hrincius, Eike R.; Liedmann, Swantje; Anhlan, Darisuren; Wolff, Thorsten; Ludwig, Stephan; Ehrhardt, Christina
Summary The non‐structural protein 1 (NS1) of influenza A viruses (IAV) encodes several src homology (SH) binding motifs (bm) (one SH2bm, up to two SH3bm), which mediate interactions with host cell proteins. In contrast to NS1 of human IAV, NS1 of avian strains possess the second SH3bm (SH3(II)bm) consensus sequence. Since our former studies demonstrated an NS1–CRK interaction, mediated by this motif, here, we addressed the regulatory properties of this SH3bm for cellular signalling. Initially, we observed a reduced basal CRK phosphorylation upon infection with avian IAV harbouring an NS1 with an SH3(II)bm in contrast to human IAV. Reduced activity of the tyrosine kinase c‐Abl was identified to be responsible for reduced CRK phosphorylation. Further, binding of NS1 to c‐Abl was determined, and mutational manipulation of the SH3(II)bm illustrated the necessity of this motif for c‐Abl inhibition. Interestingly, Abl kinase inhibition resulted in impaired avian IAV propagation and pathogenicity and mutational analysis linked the pronounced inhibition of c‐Abl to cytopathogenic cell alterations upon avian IAV infections. Taken together, NS1 proteins of avian IAV interfere with the kinase activity of c‐Abl, a major cellular signalling integrator that controls multiple signalling processes and cell fate regulations apparently including IAV infections.